Implementation Of Behavioristic And Cognitive Theories - Ahmad Baqi (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study explores the implementation of behavioristic and cognitive theories within the legal and policy framework. Behavioristic theory emphasizes observable behavior and how it is shaped by environmental stimuli, while cognitive theory focuses on internal mental processes, such as perception, thinking, and problem-solving. Both theories have significant implications for understanding human behavior, particularly in legal contexts such as criminal law, education policy, and behavior regulation. This research investigates how these psychological theories are applied in legal norms and public policies to shape behavior and decision-making. The research employs a juridical-normative approach, focusing on the legal framework and regulations that incorporate elements of behavioristic and cognitive theories. Through the analysis of laws, regulations, and policies, the study examines how these psychological principles are integrated into the creation of legal norms and the formulation of public policies. This method includes a detailed review of primary legal sources, such as statutes and policy documents, and secondary sources, including academic literature and theoretical studies. The results reveal that behavioristic theories are often applied in legal systems through punishment and reward mechanisms, aiming to modify individual behavior in criminal law and public policy. On the other hand, cognitive theories are implemented in areas that require decision-making, education, and rehabilitation, emphasizing the importance of mental processes in influencing legal outcomes. Both theories are used to achieve social control, compliance with laws, and improvement of individual decision-making processes. In conclusion, the study finds that the implementation of behavioristic and cognitive theories in law is instrumental in influencing human behavior and enhancing the effectiveness of legal systems. However, a balance between these approaches is essential to address both external behavior and internal cognitive processes in legal and policy frameworks.